2011
DOI: 10.1177/039463201102400206
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF-α Antibody (Infliximab) Therapy Supports the Recovery of eNOS and VEGFR2 Protein Expression in Endothelial Cells

Abstract: The aim of this study is to investigate the effect of sera obtained from patients of Crohn's disease treated by anti-TNF-alpha antibody (Infliximab) on the expression of endothelial nitric oxide synthase (eNOS) and vascular endothelial growth factor receptor-2 (VEGFR2) protein in human umbilical vein endothelial cells (HUVEC) cultured in vitro. HUVEC was cultured in the presence of sera derived from patients before and after treatment, or from healthy individuals. Effects of sera on the expression of eNOS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Importantly, these results obtained by Tesauro et al (2008) demonstrated that the effect of infliximab was dependent on NO synthesis. In addition, sera that were obtained from patients with Crohn's disease who were treated with infliximab induced increased eNOS expression when added to human umbilical vein endothelial cells (Altorjay et al, 2011). Our data also show that infliximab did not alter blood pressure values in normotensive WKY rats.…”
Section: Discussionsupporting
confidence: 56%
“…Importantly, these results obtained by Tesauro et al (2008) demonstrated that the effect of infliximab was dependent on NO synthesis. In addition, sera that were obtained from patients with Crohn's disease who were treated with infliximab induced increased eNOS expression when added to human umbilical vein endothelial cells (Altorjay et al, 2011). Our data also show that infliximab did not alter blood pressure values in normotensive WKY rats.…”
Section: Discussionsupporting
confidence: 56%
“…Increasing the turnover of bile salts has a beneficial effect on low-density lipoprotein cholesterol levels, which is an important risk factor for the development of atherosclerosis and playa relevant role in aging (24-29). Elevated plasma LDL cholesterol and triglyceride levels and reduced HDL cholesterol levels are associated with an increased risk of developing atheroma and shorter life (30)(31)(32)(33)(34)(35).…”
mentioning
confidence: 99%
“…Anti-TNF-α agents have also demonstrated anti-angiogenic effects in chronic inflammatory diseases such as psoriasis and Crohn’s disease. 23 , 24 By using in vitro and in vivo models, Liu et al 25 have proposed a dual mechanism to explain the anti-psoriatic effect of IBI303, an anti-TNF-α monoclonal antibody, based on the inhibition of both inflammation and angiogenesis, with a direct inhibition of the anti-TNF-α agent on blood vessel formation in vitro. Among rheumatic diseases, anti-TNF-α agents have shown anti-angiogenic properties in RA and PsA.…”
Section: Biotechnological Therapiesmentioning
confidence: 99%